Enhanced Vascular Endothelial Growth Factor Gene Expression in Ischaemic Skin of Critical Limb Ischaemia Patients. (27th March 2012) - Bleda, Silvia; de Haro, Joaquín; Acin, Francisco; Varela, César; Esparza, Leticia
Abstract : Objectives . To perform a quantitative analysis of the vascular endothelial growth factor (VEGF) gene transcription in the skin of ischemic legs and provide information for VEGF in the pathogenesis in critical limb ischemia (CLI). Methods . Skin biopsies were obtained from 40 patients with CLI. Control samples came from 44 patients with chronic venous disease. VEGF gene expression was analysed using quantitative polymerase chain reaction. Results . Patients with CLI had higher skin VEGF expression than control group (RQ: 1.3 ± 0.1 versus 1, P = 0.04 ). Conclusions . We found an association between ischemic skin and an elevated VEGF expression in legs from patients with CLI. These data support that the mechanism for VEGF upregulation in hypoxia conditions is intact and acts appropriately in the ischaemic limbs from patients with CLI.